1308. Activity of Cefiderocol and Comparators against Gram-negative Isolates from US Patients Hospitalized with Pneumonia. (4th December 2021) - Shortridge, Dee; Streit, Jennifer M; Duncan, Leonard R; Castanheira, Mariana; Castanheira, Mariana
Abstract: Background: Cefiderocol (CFDC) is a novel siderophore-conjugated cephalosporin with broad activity against Gram-negative (GN) bacteria, including carbapenem-resistant isolates, and non-fermentative organisms. CFDC is approved by the FDA for complicated urinary tract infection (cUTI), hospital-acquired bacterial pneumonia, and ventilator-associated bacterial pneumonia. In this study, we analyzed the susceptibility of CFDC and comparators against aerobic nonfastidious GN isolates collected from US patients hospitalized with pneumonia (PHP) in 2020 as a part of the SENTRY Antimicrobial Surveillance Program. Methods: A total of 1, 877 Gram-negative isolates were consecutively collected from PHP in 27 US hospitals during 2020. Susceptibility (S) testing was performed using the CLSI broth microdilution method. CFDC was tested in iron-depleted Mueller-Hinton broth. CLSI or FDA (2021) breakpoints were used. Both CLSI and FDA (2021) interpretations are shown in the table. Carbapenem-resistant Enterobacterales (CRE, nonsusceptible to imipenem and/or meropenem) and extensively drug resistant (XDR, susceptible to ≤ 2 drug classes) phenotype isolates were analyzed. Results: The most common GN organism isolated from PHP was Pseudomonas aeruginosa (PSA, n=570), followed by Klebsiella pneumoniae (n=239). The %S and MIC50/90 values of CFDC for both CLSI and FDA breakpoints and comparators are shown in the table for all organisms and resistant subsets. For Enterobacterales, all tested drugs had >99%S. The 18 CRE isolates had 94.4%S to CFDC and ceftazidime-avibactam. CFDC was the most active antimicrobial tested against PSA (99.3/98.4%S, CLSI/FDA) and XDR PSA (94.6/93.2%). CFDC had the highest %S against Acinetobacter baumannii-calcoaceticus species complex (ABC, 97.0/93.1%S, CLSI/FDA), XDR ABC (94.6/93.2%), and against Stenotrophomonas maltophilia (SM; 100.0/97.1%S, CLSI 2020/2022). Conclusion: CFDC was highly active against US GN isolates from PHP, including CRE, XDR PSA and ABC, as well as SM. These in vitro results suggest that CFDC may be an important option for the treatment of PHP caused by GN organisms, particularly for pathogens which have few treatment options. Disclosures: Dee Shortridge, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support) Jennifer M. Streit, BS, GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Leonard R. Duncan, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Basilea Pharmaceutica International, Ltd. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support, Contract no. HHSO100201600002C)Shionogi (Research Grant or Support) Mariana Castanheira, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, Affinity Biosensors (Individual(s) Involved: Self): Research Grant or Support; Allergan (Individual(s) Involved: Self): Research Grant or Support; Amicrobe, Inc (Individual(s) Involved: Self): Research Grant or Support; Amplyx Pharma (Individual(s) Involved: Self): Research Grant or Support; Artugen Therapeutics USA, Inc. (Individual(s) Involved: Self): Research Grant or Support; Astellas (Individual(s) Involved: Self): Research Grant or Support; Basilea (Individual(s) Involved: Self): Research Grant or Support; Beth Israel Deaconess Medical Center (Individual(s) Involved: Self): Research Grant or Support; BIDMC (Individual(s) Involved: Self): Research Grant or Support; bioMerieux Inc. (Individual(s) Involved: Self): Research Grant or Support; BioVersys Ag (Individual(s) Involved: Self): Research Grant or Support; Bugworks (Individual(s) Involved: Self): Research Grant or Support; Cidara (Individual(s) Involved: Self): Research Grant or Support; Cipla (Individual(s) Involved: Self): Research Grant or Support; Contrafect (Individual(s) Involved: Self): Research Grant or Support; Cormedix (Individual(s) Involved: Self): Research Grant or Support; Crestone, Inc. (Individual(s) Involved: Self): Research Grant or Support; Curza (Individual(s) Involved: Self): Research Grant or Support; CXC7 (Individual(s) Involved: Self): Research Grant or Support; Entasis (Individual(s) Involved: Self): Research Grant or Support; Fedora Pharmaceutical (Individual(s) Involved: Self): Research Grant or Support; Fimbrion Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Fox Chase (Individual(s) Involved: Self): Research Grant or Support; GlaxoSmithKline (Individual(s) Involved: Self): Research Grant or Support; Guardian Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Hardy Diagnostics (Individual(s) Involved: Self): Research Grant or Support; IHMA (Individual(s) Involved: Self): Research Grant or Support; Janssen Research & Development (Individual(s) Involved: Self): Research Grant or Support; Johnson & Johnson (Individual(s) Involved: Self): Research Grant or Support; Kaleido Biosceinces (Individual(s) Involved: Self): Research Grant or Support; KBP Biosciences (Individual(s) Involved: Self): Research Grant or Support; Luminex (Individual(s) Involved: Self): Research Grant or Support; Matrivax (Individual(s) Involved: Self): Research Grant or Support; Mayo Clinic (Individual(s) Involved: Self): Research Grant or Support; Medpace (Individual(s) Involved: Self): Research Grant or Support; Meiji Seika Pharma Co., Ltd. (Individual(s) Involved: Self): Research Grant or Support; Melinta (Individual(s) Involved: Self): Research Grant or Support; Menarini (Individual(s) Involved: Self): Research Grant or Support; Merck (Individual(s) Involved: Self): Research Grant or Support; Meridian Bioscience Inc. (Individual(s) Involved: Self): Research Grant or Support; Micromyx (Individual(s) Involved: Self): Research Grant or Support; MicuRx (Individual(s) Involved: Self): Research Grant or Support; N8 Medical (Individual(s) Involved: Self): Research Grant or Support; Nabriva (Individual(s) Involved: Self): Research Grant or Support; National Institutes of Health (Individual(s) Involved: Self): Research Grant or Support; National University of Singapore (Individual(s) Involved: Self): Research Grant or Support; North Bristol NHS Trust (Individual(s) Involved: Self): Research Grant or Support; Novome Biotechnologies (Individual(s) Involved: Self): Research Grant or Support; Paratek (Individual(s) Involved: Self): Research Grant or Support; Pfizer (Individual(s) Involved: Self): Research Grant or Support; Prokaryotics Inc. (Individual(s) Involved: Self): Research Grant or Support; QPEX Biopharma (Individual(s) Involved: Self): Research Grant or Support; Rhode Island Hospital (Individual(s) Involved: Self): Research Grant or Support; RIHML (Individual(s) Involved: Self): Research Grant or Support; Roche (Individual(s) Involved: Self): Research Grant or Support; Roivant (Individual(s) Involved: Self): Research Grant or Support; Salvat (Individual(s) Involved: Self): Research Grant or Support; Scynexis (Individual(s) Involved: Self): Research Grant or Support; SeLux Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Shionogi (Individual(s) Involved: Self): Research Grant or Support; Specific Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Spero (Individual(s) Involved: Self): Research Grant or Support; SuperTrans Medical LT (Individual(s) Involved: Self): Research Grant or Support; T2 Biosystems (Individual(s) Involved: Self): Research Grant or Support; The University of Queensland (Individual(s) Involved: Self): Research Grant or Support; Thermo Fisher Scientific (Individual(s) Involved: Self): Research Grant or Support; Tufts Medical Center (Individual(s) Involved: Self): Research Grant or Support; Universite de Sherbrooke (Individual(s) Involved: Self): Research Grant or Support; University of Iowa (Individual(s) Involved: Self): Research Grant or Support; University of Iowa Hospitals and Clinics (Individual(s) Involved: Self): Research Grant or Support; University of Wisconsin (Individual(s) Involved: Self): Research Grant or Support; UNT System College of Pharmacy (Individual(s) Involved: Self): Research Grant or Support; URMC (Individual(s) Involved: Self): Research Grant or Support; UT Southwestern (Individual(s) Involved: Self): Research Grant or Support; VenatoRx (Individual(s) Involved: Self): Research Grant or Support; Viosera Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Wayne State University (Individual(s) Involved: Self): Research Grant or Support